Under a pole star - Penney, Stef (Quercus, 2017)
A whaler's daughter, Flora Mackie first crossed the Arctic Circle at the age of twelve and fell in love with the cold and unforgiving terrain. In 1889, she sets out to become a scientist and explorer. Despite those who believe that a young woman has no place in this harsh world of men, her determination leads her back to northern Greenland at the head of a British expedition. Yearning for wider horizons, American geologist Jakob de Beyn joins a rival expedition led by the furiously driven Lester Armitage. When the path of Flora's expedition meets theirs, the three lives become intertwined. All are obsessed with the north, a place where violent extremes exist side by side: perpetual night and endless day; frozen seas and coastal meadows; heroism and lies. Armitage's ruthless desire to be the true leader of polar discovery takes him and his men on a mission whose tragic outcome will reverberate for years to come. Set against the stark, timeless beauty of northern Greenland, and fin-de-siècle New York and London, Under a Pole Star is a compelling look at the dark side of the golden age of exploration, a study of the corrosive power of ambition, and an epic, incendiary love story.